Extraction of 4-HBA utilizing renewable and conventional solvents (2024)
The valuable chemical 4-hydroxybenzoic acid (4-HBA), the phenolic compound of carboxylic acid possesses promise as an antioxidant, antifungal, anticancer, antidiabetic, and cardioprotective properties. 4-HBA has promising uses in the pharmaceutical, cosmetic, and plastic sectors, making it worthwhile to recover. Using renewable solvent like Karanja oil and traditional solvents like n-Butanol, and Di-chlorobenzene, the experimental tests were carried out to separate 4-hydroxybenzoic acid from solute mixed aqueous solution. Parameters including the distribution coefficient KD, the percentage extraction efficiency %E, the partition coefficient P, and the dimerization constant D were discovered and associated with several solvent physicochemical features while evaluating the equilibrium for this physical extraction experiment. The following parametric values were obtained for KD and %E: n-Butanol (1.704, 63.02%)> Karanja oil (0.810, 44.75%) > Di-chlorobenzene (0.555, 35.69%).